2008
DOI: 10.1111/j.1439-0396.2007.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding sorghum ergot (Claviceps africana) to sows during mid‐lactation on plasma prolactin and litter performance

Abstract: Diets containing 3% sorghum ergot (16 mg alkaloids/kg, including 14 mg dihydroergosine/kg) were fed to 12 sows from 14 days post-farrowing until weaning 14 days later, and their performance was compared with that of 10 control sows. Ergot-fed sows displayed a smaller weight loss during lactation of 24 kg/head vs. 29 kg/head in control sows (p > 0.05) despite feed consumption being less (61 kg/head total feed intake vs. 73 kg/head by control sows; p < 0.05). Ergot-fed sows had poorer weight gain of litters over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
(45 reference statements)
1
23
1
Order By: Relevance
“…In one Canadian study (Dignean et al 1986) milk production was not affected when sows were fed 0.2% rye ergot (4.5 mg alkaloids/kg of diet) from breeding until weaning, but the authors noted that their results were apparently at variance with other studies showing agalactia produced by lower ergot concentrations. Studies with sorghum ergot fed to sows before farrowing, found adverse effects on milk production at alkaloid concentrations of 1.4-7 mg/kg (Kopinski et al 2007), but higher concentrations were tolerated after lactation had commenced (Kopinski et al 2008c). Nevertheless a concentration of 0.02% rye ergot (0.4 mg alkaloids/kg) should provide an adequate safety margin for weaner and breeder pigs.…”
Section: Ergot Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one Canadian study (Dignean et al 1986) milk production was not affected when sows were fed 0.2% rye ergot (4.5 mg alkaloids/kg of diet) from breeding until weaning, but the authors noted that their results were apparently at variance with other studies showing agalactia produced by lower ergot concentrations. Studies with sorghum ergot fed to sows before farrowing, found adverse effects on milk production at alkaloid concentrations of 1.4-7 mg/kg (Kopinski et al 2007), but higher concentrations were tolerated after lactation had commenced (Kopinski et al 2008c). Nevertheless a concentration of 0.02% rye ergot (0.4 mg alkaloids/kg) should provide an adequate safety margin for weaner and breeder pigs.…”
Section: Ergot Alkaloidsmentioning
confidence: 99%
“…The tolerance of nonlactating pigs is also not clear but a Canadian study (Oresanya et al 2003) suggested maximum tolerances of 0.1% ergot (2 mg alkaloid/kg) and 0.05% based on growth rates and feed intakes respectively for weaner pigs (7-20 kg liveweight). Other studies have shown that grower and finisher pigs are more resistant and 10-15 mg/kg can be tolerated with only minor effects on feed intakes that can be masked with palatable ingredients (Whittemore et al 1977;Mainka et al 2005;Kopinski et al 2008aKopinski et al , 2008bKopinski et al , 2008c. One Australian study (Bakau et al 1988) found reductions in growth rate and feed intake of pigs fed 0.75% ergot (alkaloid content not reported), which were exacerbated by higher temperatures (35 C).…”
Section: Ergot Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect on milk production is caused by prolactin inhibition (Whitacre and Threlfall, 1981;Kopinski et al, 2007). A concentration of 0.3% sclerotia in the lactation feed is sufficient to cause agalactia in 50% of sows.…”
Section: Ergot Alkaloidsmentioning
confidence: 99%